Open research in laboratory practice to learn Chemistry in high school students - Faicán-Juca, Fernanda (2024)
Experimentation as a methodological strategy used in the teaching-learning process in chemistry presents a stagnation in the acquisition of knowledge, skills, and indispensable abilities. Currently, practices are based on methodically following the procedure given in a laboratory guide, causing a passive learning, where the student is not directly involved in building their own knowledge. For this reason, the purpose of this study was to apply open research in laboratory practice, since it is a methodology based on constructivist learning. Its relationship with the learning of chemistry was investigated, in addition to determining its influence and identifying its contribution to it. This research was non-experimental and correlational in scope. On the other hand, a survey and an evaluation test were applied to 125 high school students of the Nuestra Familia Educational Unit. As main results, a positive, moderate, and significant correlation was obtained between the open investigation in the laboratory practice with the learning of Chemistry. In addition, the results of the evaluation test show a positive influence by obtaining 75% of students who reach and master the learning. While 73.60% of students consider that the open research contributes considerably in the acquisition of learning. As a consequence, the applied methodology presents a superior cognitive contribution by developing and strengthening the research process and executing it in the laboratory.